Winning the transglobal leadership how to find and develop top global talent to build world-class organizations - Sharkey, Linda D. (McGraw Hill, 2012)
Operating and expanding business units offshore, selling in foreign markets, and managing global supply chains are just three of the many challenges that emphasize the importance of leaders that can transcend borders. Winning with Transglobal Leadership will help prepare your organization to meet this need head-on with a framework for developing and training leaders that best fit your global growth strategies. The book combines insights from a global team of author-experts. Together, they draw on an impressive range of resources-extensive original research, interviews with world-class high-performing executives, and decades of combined experience as senior executives, researchers, and consultants-to deliver an easily implemented process for assessing your organization's global capability and developing the leaders who will drive success. Inside Winning with Transglobal Leadership, you will find: - Guidance on measuring and evaluating your organization's capacity to compete globally - Five behavioral dimensions that global leaders need to develop - Keys to assessing leadership candidates early in their careers - The "Transglobal Leadership Matrix," a tool for taking stock of your own skills and behaviors At a recent World Economic Forum in Davos, Switzerland, numerous CEOs in attendance cited a growing need for talent that could function successfully in new and emerging global markets. For leaders and managers, HR and training specialists, or anybody doing business today, Winning with Transglobal Leadership is the definitive handbook on satisfying the demand for specialized leadership skills-now and in the years to come.